The cooler [videorecording (DVD)] - Isham, Mark (Lions Gate Home Entertainment, 2004)
Bernie is extremely unlucky at gambling and he owes the Shangri-La casino's mob boss Shelly Kaplow over $100,000. He is so unlucky that he is hired as a "cooler". He gambles next to high rollers and gives them some of his bad luck to stop them from winning. This arrangement works out for awhile, but when Bernie has almost paid off his debt, he meets cocktail waitress, Natalie. The two start to fall in love and Bernie's luck begins to change. Unfortunately, Shelly isn't going to let Bernie go so easily